Study of siltation intensity of water reservoir (Международный научный журнал «Инженер», 2026)
Reservoirs play an important role in providing water for agriculture and generating energy. After thereservoirs are filled, morphometric changes occur in the reservoir area during operation. As the reservoirfills, the flow rate decreases, resulting in accumulation of suspended sediments and bottom sediments inthe stream. Large sediments are concentrated in the upper part, while fine sediments are distributed inthe middle and lower parts as the flow velocity decreases, and the size of the mud fractions graduallydecreases towards the dam. The article analyses the dynamics of turbidity during the operation of thereservoir using the example of the TMGU O’zan reservoir. The volume of turbidity in 1981-2001 wasapproximately 1145 million tons, and by 2021 it reached 1744 million tons. Considering the averagedensity of the settling turbidity, today 790 million m3 of the volume is filled with turbidity, which meansthat 35% of the volume of the O’zan reservoir is filled with turbidity.